Determinants of ESG Disclosure in the Energy Sector: The Influence of Foreign Ownership, ROA, and Firm Size (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study examines the influence of foreign ownership, return on assets (ROA), and firm size on environmental, social, and governance (ESG) disclosure among energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The sample was selected through purposive sampling, including firms that consistently published annual and sustainability reports in accordance with the Global Reporting Initiative (GRI) standards. ESG disclosure was measured as the proportion of disclosed GRI indicators to the total applicable indicators. Multiple linear regression analysis shows that foreign ownership and firm size significantly enhance ESG disclosure, while ROA has no significant effect. These results support legitimacy theory, suggesting that companies increase ESG transparency primarily to secure societal acceptance and maintain their social license to operate. In the energy sector, where environmental sensitivity and public scrutiny are high, ownership structure and firm scale emerge as stronger determinants of ESG disclosure than short-term profitability.